Doctor-patient interaction and informed consent in pediatric surgery: theory and reality in the regional practice - Sergio Luis González López; Carlos Alberto Cabrera Machado; Guillermo Cortiza Orbe; Zoe Quintero Delgado; Bertha Emelina Fonseca Romero; Yordan Ponce Rodríguez (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2009)
Informed consent is a core element in the doctor-patient interaction. With the objective of reviewing the essentials and legal basis of its procedure and relation with pediatric surgery in the regional context we developed a bibliographic review of national and international biomedical publications. It is widely accepted that the recognition of patient´s autonomy and the informed consent process have led to a change in the doctor-patients interaction, which is closely linked to the pediatric surgical practice in the particular Cuban modern environment. In addition to the study of bioethical principles and their enforcement by those who are to provide medical services, it is also necessary to look for useful answers to bioethical questions affecting the legal tools that support the procedure.